Poetics of Disturbances : Narratives of Non-normative Bodies and Minds - Jumpertz, Jessica; Muijnck, Deborah de; Schneider, Ralf; Turnbull, Teresa (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
This volume calls for a Narratology of Diversity by investigating narratives of non-normative bodies and minds. It explores mental health representations in literature, including neurodiversity, the body-mind nexus, and embodied non-normativities, therein emphasizing the importance of understanding diverse psychological conditions as represented in narratives. The contributions include perspectives from a wide variety of scholars of European, North American, and comparative literature and culture. While post-classical narratology has evolved through phases of diversification and consolidation, this volume represents innovation in understanding narrative development to embrace new areas of social awareness, including gendered narratologies (specifically feminist and queer narratologies) and post-colonial criticism, paving the way for a more inclusive narratology. See Less